Implementasi Algoritme Grain V1 Pada Protokol MQTT Menggunakan Raspberry Pi Untuk Mengamankan Data IoT - Iskar Maulana; Ari Kusyanti; Adhitya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Internet of Things (IoT) is one of the most commonly used technologies today because IoT can connect various devices. In general, the protocol used in IoT is the MQTT protocol that utilize wireless as a medium for data exchange. However, wireless media is vulnerable to wiretapping. Data threats become an unavoidable so there is a need secure the data. One technique for securing data is Grain v1 algorithm. This algorithm is an algorithm in cryptography that is used to encrypt and decrypt messages. The author uses Raspberry Pi as a publisher and subscriber as well as a Virtual Machine (VM) as a broker. The Grain v1 algorithm is placed on each client (publisher and subscriber) so that when the payload is transmitted over the MQTT protocol, the data contained in the payload is encrypted. Likewise, the payload is decrypted after it is received by the subscriber. There are 5 tests to ensure that the system works well including test vector validation testing, system functional, validation testing, encryption and decryption results, sniffing, and time performance. The result shows that test vector validation, encryption and decryption process validation are valid. Functional test shows that system can run well. Based on sniffing test, the payload cannot be read by unauthorized party. Finally, the execution time of processing keystream, encryption and decryption take 0.01246 second, 0.01627 second, and 0.02238 second.